Formulation and Clinical Evaluation of Anti-Aging Activity of Blemish Balm Cream Vitamin E and Determination of SPF Value with Spectrophotometry - Siregar, Citra Sari Dewi; Reveny, Julia; Dalimunthe, Aminah (Asian Journal of Pharmaceutical Research and Development, 2019)
Objective: to formulate face powder and foundation cream preparations into Blemish Balm Cream preparations with the addition of vitamin E, avobenzone and octyl methoxoxycinamic acid and to determine the effect of vitamin E on anti-aging activity and SPF values. Design: Blemish Balm Cream formulated from face powder and foundation cream in a ratio of 1: 2 and the addition of vitamin E in various concentrations, F0 (blank), F1 (1%); F2 (3%), and F3 (5%) and Avobenzone 3% sunscreen and 7.5% Octylmethoxycinamic. Interventions: the intervened variable was the concentration of vitamin E used. Main outcome measures: the main measurement in this study were organoleptic test (shape, color and odor), homogeneity, pH, type of emulsion, viscosity, cycling test, spreadability, storage stability at room temperature, low temperature and high temperature for 12 weeks, irritation test, anti-activity aging with skin analysis and determination of SPF values ​​by UV-Vis spectrophotometry. Results: The Formulated Blemish Balm Cream was homogeneous, yellowish brown, has an emulsion type m / a, stable in room temperature storage (20-25 ° C), unstable in low temperature (4 ± 2 ° C), and high temperature ( 40 ± 2 ° C), had a pH of 6.0-7.9, produces a viscosity value that meets the requirements, was stable in the cycling test and did not irritate the skin. The results of anti-aging activity on F3 (5%) had a better effect than F0 (blank), F1 (1%) and F2 (3%) which characterized by increased skin moisture, pore reduction, reduction in the number of blemishes and reduction in wrinkles and produced higher SPF value. Conclusion: Vitamin E (5%) and avobenzone 3% sunscreen and 7.5% octylmethoxycinamic could formulated into Blemish Balm Cream preparations used face powder and foundation formulas (1: 2) and provided good anti-aging activity effects, did not irritate the skin and could increased the value of the Sun Protecting Factor to 22.21